Promoting Universal Design in Public Buildings: An Action Research Study of Community Participation - Copeland, Elise (Auckland University of Technology, 2014)
The design of many public buildings poses significant barriers to the full and equal participation of all members of society. Building users have valuable experiential knowledge of barriers to accessibility through their interactions with buildings, though this is frequently overlooked by professionals. A literature review highlighted the limited success of professionals in promoting universal design in buildings. The review also revealed an approach to engaging with building users which offered an alternative strategy worthy of further exploration. Lack of collaboration with building users to analyse public buildings according to universal design principles was identified as a research gap. The research question guiding this study was: how can users influence the universal design of public buildings? Seven diverse participants were purposively recruited as co-researchers from a range of advocacy organisations. The co-researchers came together for a series of six meetings based on the search conference method, which involves creating a shared history and future vision, identifying and prioritising action plans for addressing the problem, and initiating change activities. In addition to the search conference, the co-researchers assessed a public library using a universal design assessment tool as a means of experiential learning of the universal design principles. The action research process points to three mechanisms by which building users may be able to influence the universal design of public buildings: by forming a group, by using a formal assessment tool and by presenting their views. Forming a group enabled the co-researchers to broaden their perspectives and share their knowledge, skills, networks and resources amongst the group. The universal design assessment tool enhanced the co-researchers’ learning of the universal design principles and equipped them to assess universal design. By presenting their views the co-researchers gained access to new networks, reflected on ways of influencing change and reflected on how change in governance impacts on community participation. This study empowered users of public buildings to assess environmental barriers using universal design principles and to promote positive social change to enhance community participation. The primary limitations of this study involve recruitment. There were a small number of community advocates as co-researchers, which means that the findings of this study cannot be generalised to other groups, nor the other stakeholders that may influence or benefit from universal design in public buildings. Further research is warranted to investigate how the wider stakeholders involved in the design of public buildings may influence their universal design now and into the future.
Keywords: Universal design; Public buildings; Action research; Search conference; Inclusive design; Participation